AUTHORITY OF SERVICE INSTITUTION MANAGEMENT AUTONOMY HEALTH IN SUMENEP DISTRICT - Ahmad Suwaifi Qayyum (DIA: Jurnal Administrasi Publik, 2023)
A new paradigm of government management has been carried out in Indonesia with the Public Service Agency/Regional Public Service Agency (BLU/BLUD) program with the issuance of the Peraturan Pemerintah Nomor 23 Tahun 2005. Public services are not only a new form of state financial management but also a new paradigm for public sector service management (Lestari, et al, 2019). The Puskesmas is the spearhead of the leading health services. The existence of a health center is very necessary to improve the health status of the community. The Puskesmas has various functions, one of the main functions and tasks of the Puskesmas is to provide basic health services to the community in its working area which is most widely used by the middle to lower class of society. In order for the puskesmas to carry out its functions optimally, various efforts to provide autonomy for the management of the puskesmas have been carried out according to existing regulations. Through this policy, puskesmas are given the authority to use the income they earn directly to finance operational activities, maintenance activities and improve human resource capabilities.